2021
DOI: 10.33448/rsd-v10i7.16454
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação microbiológica de maioneses artesanais fornecidas em serviços de alimentação do centro de Campina Grande - PB

Abstract: Com consumo elevado em lanchonetes da cidade a maionese é um produto feito à base de óleo, água e ovos; utilizada para realçar o sabor dos alimentos, podendo ser encontrada em diversas formas para uso. Em Campina Grande, muito se tem empregado a maionese de forma artesanal com adição de temperos naturais como forma de atrair ainda mais o paladar da população, o que torna esta prática uma fonte propícia para a contaminação do produto devido ao processo de manipulação. Com o objetivo de avaliar e quantificar a q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(7 reference statements)
0
0
0
Order By: Relevance
“…60 (December 23, 2019), which state that mayonnaise must be absent of Salmonella (Brasil, 2019a, b). Other studies of homemade mayonnaise found similar results; most samples showed high contamination by pathogenic microorganisms (Santos et al, 2021;Felinto et al, 2021). Santos et al (2021) observed contamination in properly refrigerated samples of homemade mayonnaise, indicating that it had been prepared under poor sanitary standards.…”
Section: Resultsmentioning
confidence: 58%
“…60 (December 23, 2019), which state that mayonnaise must be absent of Salmonella (Brasil, 2019a, b). Other studies of homemade mayonnaise found similar results; most samples showed high contamination by pathogenic microorganisms (Santos et al, 2021;Felinto et al, 2021). Santos et al (2021) observed contamination in properly refrigerated samples of homemade mayonnaise, indicating that it had been prepared under poor sanitary standards.…”
Section: Resultsmentioning
confidence: 58%